From Fugitives to Ferguson: Repairing Historical and Structural Defects in Legally Sanctioned Use of Deadly Force - José Felipé Anderson (Washington University Journal of Law & Policy, 2015)
This Article proposes a number of solutions to help make policing more professional and accountable. Anderson discusses the troubling structural connection between slavery and law enforcement, and argues that courts’ use-of-force cases have not adequately incentivized safer policing. Instead, he suggests police officers should lose their qualified immunity in circumstances either by way of judicial enforcement or legislation.
Keywords: police brutality; police accountability; law enforcement